2015
DOI: 10.1007/s11606-015-3285-7
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Use of Colchicine after FDA Enforcement of Market Exclusivity in a Commercially Insured Population

Abstract: BACKGROUND: A brand-name version of colchicine (Colcrys) was introduced after its manufacturer conducted a clinical trial in acute gout patients, leading to higher prices for this drug. OBJECTIVE: We analyzed the impact of the new singlesource colchicine product on prescribing and patient health spending as well as incidence rates of potentially dangerous concomitant use of clarithromycin and cyclosporine after formal FDA approval. DESIGN/PARTICIPANTS: We conducted a retrospective cohort study of UnitedHealth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The continuing decline in NSAID use observed in our study was contrasted by a modest increase in both colchicine and glucocorticoid use among gout patients over the study period. By comparison, a recent US-based study reported an increasing trend of colchicine initiation among those with newly diagnosed gout until the medication's substantial price increase in the US, after which colchicine initiation declined [42, 43]. Meanwhile, such a decline was not observed in the current Canadian setting where colchicine remains at its original low cost.…”
Section: Discussionmentioning
confidence: 99%
“…The continuing decline in NSAID use observed in our study was contrasted by a modest increase in both colchicine and glucocorticoid use among gout patients over the study period. By comparison, a recent US-based study reported an increasing trend of colchicine initiation among those with newly diagnosed gout until the medication's substantial price increase in the US, after which colchicine initiation declined [42, 43]. Meanwhile, such a decline was not observed in the current Canadian setting where colchicine remains at its original low cost.…”
Section: Discussionmentioning
confidence: 99%
“…We extracted population-level data on prevalent statin use from the Optum Clinformatics research database, which covers 14 mil-lion current beneficiaries insured under UnitedHealth Group. [7][8][9][10] Eligible patients were 18 years or older, had at least 180 days of continuous enrollment, and had filled a prescription for at least 1 statin (atorvastatin, simvastatin, rosuvastatin, fluvastatin, pitavastatin, lovastatin, pravastatin, combined amlodipine besylate and atorvastatin, combined ezetimibe and simvastatin, combined atorvastatin and ezetimibe, combined niacin and simvastatin, or combined niacin and lovastatin) from December 1, 2010 (1 calendar year before the first generic entry), to May 31, 2013 (1 calendar year after full generic competition). This study was approved by the institutional review board of Brigham and Women's Hospital and Harvard Medical School, which waived the need for informed consent for the deidentified patient data.…”
Section: Data Source and Patient Populationmentioning
confidence: 99%
“…Previous articles have explored the historical background for the UDI 3,8,9 and characterized the experience of individual unapproved drugs, 3,[8][9][10][11][12] including the finding that prices and shortages of specific drugs increased after they were targeted by the UDI. [13][14][15][16][17] However, to…”
Section: Clinical Evidencementioning
confidence: 99%